Java plum and amaltash seed biomass based bio-adsorbents for synthetic wastewater treatment - Giri D.D.; Jha J.M.; Tiwari A.K.; Srivastava N.; Hashem A.; Alqarawi A.A.; Abd_Allah E.F.; Pal D.B. (My University, 2025)
Biomass of Java plum (JP) and amaltash (AT) seeds were employed to remove arsenic from synthetic wastewater, cost effectively. The prepared biomasses were characterized by FE-SEM, EDX, FTIR, XRD, and ICP techniques. Experimentation the optimization study has been carried out by using Design-software 6.0.8. Response surface methodology has been applied to design the experiments where we have used three factors and three levels Box-Behnken design (BBD). Arsenic removal ability of bio-sorbents was evaluated and optimized by varying pH, adsorbent dose concentration of arsenic in synthetic wastewater. For 2.5 mg/L arsenic concentration and 80 mg adsorbent dose at pH 8.8 Java plum seeds (JP) based bio-adsorbent removed ∼93% and amaltash seeds (AT) based bio-adsorbent removed ∼91% arsenic from synthetic wastewater. The adsorption behaviour better explained following Freundlich model (R2 = 0.99) compared to Temkin model (R2 = 0.986) for As (III) ions. The adsorption capacity was 1.45 mg g−1 and 1.42 mg g−1 for JP and AT, respectively after 80 min under optimal set of condition. The adsorption kinetics was explained by either pseudo-first order model or Elovich model. © 2021 Elsevier Ltd; The locally available plant seeds of Java Plum and Amaltash used for preparing bio-sorbents showed arsenic removal 93% and 91% in synthetic wastewater following Freundlich adsorption model (R2 = 0.99) and kinetics pseudo-first order model or Elovich model. The low-cost material freely available in villages can potentially solve the issue of As pollution in water, if bio-sorbent could be prepared locally. © 2021 Elsevier Ltd